2000
DOI: 10.1159/000054276
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NK Cell Activity and of Resistance to Metastasis by Stress: A Role for Adrenal Catecholamines and β-Adrenoceptors

Abstract: Although acute stress has been reported to suppress natural killer cell activity (NKA) and host resistance to metastasis, it is unclear whether the sympathetic nervous system (SNS) has a role in these effects. The current study in Fischer 344 rats assessed the involvement of adrenal catecholamines and β1- and β2-adrenoceptors in mediating these deleterious effects of swim stress. In addition to assessing the number and activity of NK cells following swim stress, we used a tumor model base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 61 publications
5
126
1
2
Order By: Relevance
“…Beta-adrenergic signaling has an important role in the initiation and progression of cancer, affecting inflammation, angiogenesis, apoptosis, cell migration, DNA damage repair and the epithelial-mesenchymal transition (Cole and Sood, 2012). Another explanation for the association of beta-adrenergic signaling with cancer growth may be related to the immune system (Ben-Eliyahu et al, 2000). Norepinephrine and beta-AR signaling have strong stimulating effects on a number of cancer types, including cancers of the colon (Masur et al, 2001;, prostate (Palm et al, 2006), ovary (Sood et al, 2006;Thaker et al, 2006), breast (Drell et al, 2003) and pancreas .…”
Section: Discussionmentioning
confidence: 99%
“…Beta-adrenergic signaling has an important role in the initiation and progression of cancer, affecting inflammation, angiogenesis, apoptosis, cell migration, DNA damage repair and the epithelial-mesenchymal transition (Cole and Sood, 2012). Another explanation for the association of beta-adrenergic signaling with cancer growth may be related to the immune system (Ben-Eliyahu et al, 2000). Norepinephrine and beta-AR signaling have strong stimulating effects on a number of cancer types, including cancers of the colon (Masur et al, 2001;, prostate (Palm et al, 2006), ovary (Sood et al, 2006;Thaker et al, 2006), breast (Drell et al, 2003) and pancreas .…”
Section: Discussionmentioning
confidence: 99%
“…The perioperative administration of propranolol and other b-blockers have been frequently used to prevent surgery related cardiac complications and mortality (49). We used a nonselective b-antagonist (propranolol), as human leukocytes and human tumor cells express both b-1 and b-2 adrenoceptors (50, 51), and as our previous study indicated that the blockade of both receptor systems was more effective than each alone in preventing stress-induced promotion of metastasis (52). Importantly, in the clinical setting of oncologic surgery, the drug regimen used in this study may be even more efficient if initiated a few days before surgery, because etodolac could reduce PGs release by primary tumors (14); propranolol could reduce anxiety (53) and antagonize the excess release of CAs owing to preoperative physiologic and psychologic stress responses (54,55).…”
Section: Sectionmentioning
confidence: 99%
“…These effects are thought to be mediated in part by the sympathetic nervous system, the HPA axis, and a variety of other hormones and peptides [8,[10][11][12][13]. In both animal and human studies, chronic stress has been shown to decrease cellular immune parameters, such as natural killer (NK) cell cytotoxicity and T-cell responses to mitogen stimulation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%